Morphological, anatomical, and physiological changes of orchardgrass leaves grown under fluctuating light regimes - Peri, Pablo Luis; Moot, Derrick; Jarvis, Peter; McNeil, David L.; Lucas, R.J. (Wiley, 2025)
The physiological and anatomical adaptability of pastures growing under trees in silvopastoral systems can alter the efficiency of conversion of energy to dry matter (DM). This study was conducted to determine the effects of different fluctuating light regimes (from 24 to 100% transmissivity) on leaf physiology, morphology, anatomy, and structure of orchardgrass (Dactylis glomerata L.) in a silvopastoral experiment (New Zealand). Slatted shade structures created a bimodal light regime that represented an existing silvopastoral system. Morphologically, as transmissivity decreased the length of the youngest fully expanded leaf and pseudo-stem height increased by up to 33% and the leaf width declined up to 22%. Physiologically, leaf adaptation to different light regimes was characterized by: (i) the light-saturated rate of net photosynthesis (Pmax) and to less extent the photosynthetic efficiency (a) in sun conditions was double; (ii) in sunny conditions plants grown under shade were photosynthetically less efficient than plants grown in full sunlight with lower Pmax and a values; (iii) when plants were exposed to severe shade, leaves adapted to severe shade condition had the highest Pmax, a, and u, and saturated at the minimum photosynthetic photon flux density (PPFD) value. These changes in leaf photosynthesis characteristics under different light regimes were attributed to anatomical changes that caused reductions in stomatal conductance (gs), the mesophyll surface area/leaf surface area ratio (Ames/A) and maintenance respiration for shade adapted plants. These photosynthetic responses and leaf adaptations to fluctuating light regimes can be included into a canopy photosynthesis model to improve the accuracy of DM predictions in silvopastoral systems.